2021
DOI: 10.21203/rs.3.rs-427122/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relation Between Malnutrition and the Presence of Symptoms of Anxiety and Depression in Hospitalized Cancer Patients

Abstract: BackgroundAnxiety and depression are a common issue in patients with cancer, yet understudied among hospitalized patients. The aim of this study was to estimate the prevalence of anxiety and depression symptomatology in cancer inpatients and its relationship with malnutrition. MethodsCross-sectional study in hospitalized cancer patients. A nutritional assessment was done using GLIM criteria to diagnose malnutrition. Data regarding anxiety and depression symptomatology was obtained with the Hospital Anxiety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
1
0
1
Order By: Relevance
“…In contrast, our finding did not find a significant effect on the quality of life, readmission events or the number of medication despite the decreased anxiety and depression levels in the intervention group that could have been attributed to the accompanying volunteers during the dinner. In a recently published study, S anchez-Torralvo and colleagues [34] found a significant association between malnutrition and the levels of anxiety and depression in older hospitalized cancer patients [34]. Patients suffering from depression tend to eat smaller quantities of low-quality food and therefore lose weight and muscle, in turn contributing to the development of malnutrition [35].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our finding did not find a significant effect on the quality of life, readmission events or the number of medication despite the decreased anxiety and depression levels in the intervention group that could have been attributed to the accompanying volunteers during the dinner. In a recently published study, S anchez-Torralvo and colleagues [34] found a significant association between malnutrition and the levels of anxiety and depression in older hospitalized cancer patients [34]. Patients suffering from depression tend to eat smaller quantities of low-quality food and therefore lose weight and muscle, in turn contributing to the development of malnutrition [35].…”
Section: Discussionmentioning
confidence: 99%
“…Alguns pacientes que apresentam perda de peso e outros sintomas de desnutrição geralmente relatam níveis mais elevados de sofrimento psicológico, que se manifestam como: insônia, ansiedade e depressão, podem contribuir para a progressão da doença. O medo de algo novo gerado na criança pode afetar negativamente seu consumo alimentar, aumentando assim o risco de desnutrição (Torralvo et al, 2022) O desenvolvimento da desnutrição em pacientes hospitalizados é alto, principalmente em crianças, devido ao aumento da necessidade energética decorrente da patologia que a criança se encontra, a diminuição do apetite devido a ansiedade que o ambiente hospitalar pode gerar, juntamente ao uso de medicamentos (Beser et al, 2018).…”
Section: Introductionunclassified